Hubungan Tingkat Stress Dalam Menghadapi Pandemi Covid-19 Dengan Angka Kejadian Gerd di Puskesmas Pandan, Kecamatan Pacet, Kabupaten Mojokerto Pada Bulan September Tahun 2021 - Eva Ma'rifatus Syadiyah; Nini Primadhani Paras Shinta Dewi; Kadek Cahya Adwitiya; Gede Utama Diatmika Putra; Ayu Cahyani Noviana (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2022)
During the Covid-19 pandemic, it affected many people's lives, one of which had an impact on the socio-economic community. the deflation of Income and outcome causes anxiety whicheventually leads to increased stress. Stress can affect changes in the function of the digestive system where stress reduces appetite thereby increasing stomach acid, causing pain in the stomach which causes GERD. The research design used a correlation analytic design using a cross sectional approach. Determination of the population in this study using purposive random sampling and obtained a suitable data source as many as 30 research samples. The data collection technique used is a questionnaire. The data analysis method used is the Contingency Coefficient Test using SPSS. The results showed that 53.3% of respondents had GERD, and 46.7% of those who did not have GERD. Respondents with normal stress with GERD were 2 respondents (6.7%). Respondents with mild stress conditions with GERD 4 respondents (13.3%). Respondents with moderate stress conditions with GERD 2 respondents (6.7%). Respondents with severe stress conditions with GERD 8 respondents (26.7%). From the chi-square statistical test, p = 0.00 (α < 0.05) and there is a relationship between stress and the incidence of GERD. Based on the contingency coefficient test, it shows C = 0.669, meaning that the level of relationship between the influence of stress and the incidence of GERD is in the strong category.